The frequency and clinical and endoscopic features of mixed NSAIDs-induced gastrointestinal injuries - A. P. Balabantseva; A. E. Karateev (Современная ревматология)
Non-steroidal anti-inflammatory drugs (NSAIDs) can cause undesirable reactions in all parts of the gastrointestinal tract (GIT). However, the frequency of mixed injuries of various GIT parts due to the use of these drugs has not been investigated.Objective: to estimate the frequency of mixed NSAID-induced injuries of the upper GIT, small and large intestine.Patients and methods. A total of 112 patients (62.5% were women) (mean age, 56.2±14.6 years) with rheumatic diseases who had regularly taken NSAIDs were examined. All the patients underwent esophagogastroduodenoscopy and video colonoscopy. Video capsule endoscopy was performed in 35 patients with signs of NSAID-induced gastropathy.Results and discussion. The signs of NSAID-induced gastropathy (gastric and duodenal erosions and/or ulcers) were found in 43.8% of patients; those of NSAID-induced enteropathy (small bowel hemorrhages, erosions, and ulcers) were present in 68.6%; and those of NSAIDinduced colopathy (colonic hemorrhages, erosions, and ulcers) were in 14.3%. The concurrence of NSAID-induced gastro- and colonopathy was present in 28.6% of the patients (odds ratio 12.2; 95% confidence interval, 2.619–56.84); that of NSAID-induced gastro-, entero-, and colopathy was in 10 (20.4% of all the patients with NSAID-induced gastropathy). There was a significant association of the risk of mixed pathology in all GIT parts with the diagnosis of spondylarthritis, the presence of abdominal pain, the signs of dysbiosis and bacterial overgrowth syndrome, as well as with the carriage of CYP2C19 gene polymorphism (the CYP2C19*17*1/*17 allele).Conclusion. Mixed injury of various GIT parts due to the use of NSAIDs is a frequent and serious pathology that requires comprehensive diagnostic tests and combined use of preventive therapies with different mechanisms of action.